Effects of Lugol's iodine on long-term preservation of marine plankton samples for molecular and stable carbon and nitrogen isotope analyses - Sano, Masayoshi; Makabe, Ryosuke; Kurosawa, Norio; Moteki, Masato; Odate, Tsuneo (Limnology and Oceanography: Methods, 2020)
Carbon and nitrogen stable isotope and molecular analyses are common tools for marine ecological and biological research. However, it is difficult to fix samples for both analyses using only one preservative. A solution of potassium iodide and iodine (known as Lugol's iodine solution) is considered to be a suitable preservative; however, the effectiveness of Lugol's iodine solution for long-term preservation of samples for stable isotope analysis and molecular analysis has not yet been investigated. We tested the effectiveness of 5% and 10% Lugol's iodine solutions by comparing them with marine plankton samples preserved in a 5% formalin solution, as well as preserved by freezing. Although δ13C and δ15N values of samples fixed in 5% formalin and 5% Lugol's iodine solution were significantly different from those of frozen samples, there were no significant differences in both δ13C and δ15N values between samples fixed in 10% Lugol's iodine solution and frozen samples, when preserved for a duration from 1 week up to 6 months. Polymerase chain reaction (PCR) assay of samples fixed in 10% Lugol's iodine solution after 18 months of preservation succeeded; however, the DNA in samples fixed in 5% formalin and 5% Lugol's iodine solution could not be amplified using PCR. There was no difference in the sequences of partial 18S rRNA genes between samples fixed in 10% Lugol's solution and frozen samples. Thus, we conclude that 10% Lugol's solution is a suitable fixative for both of carbon and nitrogen stable isotope and molecular analyses. 17H06319 journal article